SAT0033 The Clinical Application of Detection of Antinuclear Antibodies Spectrum Eighteen Items in Systemic Lupus Erythematosus. (10th June 2014) - Ye, Z.; Yin, Z.; He, W.; Luo, X.
Abstract : Objectives: To explore the clinical application value of detection of antinuclear antibodies (ANA) spectrum eighteen items in the diagnosis and treatment of systemic lupus erythematosus (SLE). Methods: ANA spectrum eighteen item were detected with indirect immunoflurescence and immunoblotting methods. The results of ANA spectrum in 370 inpatients cases of our hospital were retrospectively analyzed, including SLE patients (158 cases), other autoimmune diseases patients (142 cases) and other diseases patients (70 cases). Results: The positive rate of ten antibodies of ANA spectrum eighteen items showed significant defference between SLE group with other autoimmune diseases group and other diseases group, including ANA (96.84%, 55.47%, 27.10%; P<0.01), Anti-SSA/Ro60 (55.06%, 14.34%, 3.39%; P<0.01), Anti- SSA/Ro52 (46.20%, 12.83%, 1.69%; P<0.01), Anti-SmD1 (31.65%, 2.64%, 1.69%; P<0.01), Anti- U1-snRNP (25.95%, 2.26%, 0%; P<0.01), AnuA (25.32%, 0.75%, 0%; P<0.01), Anti- SSB/La (25.32%, 5.66%, 0.85%; P<0.01), Anti-dsDNA (24.05%, 0.38%, 0%; P<0.01), AHA (20.89%, 0.38%, 0%; P<0.01), Anti-P0 (18.35%, 0.38%, 0%; P<0.01) Conclusions: The detection of ANA spectrum eighteen items is valuable on the screening and diagosis of SLE. References: Cortes-Hernandez J, Ordi-Ros J, LabradorM, et al. Anti-histone and anti-double-stranded deoxyribonucleic acid antibodies are associated with renal disease in systemic lupus erythematosus. Am J Med 2004;116:F165. Hung WT, Chen YM, Lan JL et al. Anti-nucleosome antibodies as a potential biomarker for the evaluation of renal pathological activity in patients with proliferative lupus nephritis. Lupus 2011;20(13):1404-1410. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1719